Analisis strategi food coping keluarga dan penentuan indikator kelaparan - Erli Mutiara; Hidayat Syarief; Ikeu Tanziha; Dadang Sukandar (Media Gizi dan Keluarga, 2008)
ABSTRACT. The research objectives were to analyze strategies in family food coping and to determine hunger indicators. The research design was retrospective and it was conducted in two difference area representing rural community (Village of Suka Maju, Cibungbulang District, Bogor Regency) and urban community (Village of Suka Resmi, Tanah Sareal District, Bogor Municipality), both in West Java Province. Samples of 120 poor families were drawn randomly out of 3340 families from both areas. The primary data was collected from samples using questionnaire which consist of food coping strategy, hunger indicator. The discriminant analysis to determine of hunger indicators. The results showed that the proportion of family suffering from hunger was 29.2 %. There were the differences in food coping strategies between the group of hunger and non-hunger families. The discriminant analysis based on the single variable showed that the family's hunger indicator was skipping eating for whole days. By the two variables, the hunger indicators were skipping eating for whole days, and reducing the habitual of food frequency. However by applying the one and two variables, the result of misclassifications were similar, Jl.47% hunger families classified into non-hunger families and 24.71% non-hunger families categorized into hunger ones.Key words : Food coping strategy, hunger indicator, family